Monolithic adsorbent based on 3D printing technology, preparation method and low-temperature cold start application of monolithic adsorbent
The Mn/Al2O3 integral adsorbent prepared through 3D printing technology is connected in series with the SCR processing unit, which solves the high cost of precious metal adsorbent and the problems existing in 3D printing of Mn/Al2O3 powder materials, and realizes NOx in the cold start stage of diesel vehicle Ultra-low emissions and economic benefits of adsorbents.
Patent Information
- Application Number
- CN202410965409.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-07-18
AI Technical Summary
The existing precious metal load adsorbents have high cost and short service life, making it difficult to achieve ultra-low NOx emissions in the cold start stage of diesel vehicles, and Mn/Al2O3 powder materials have problems of structural unevenness and poor mechanical strength during the 3D printing process.
The integrated non-precious metal adsorbent was prepared by 3D printing technology, using Mn/Al2O3 powder, Elosite nanotubes and hydroxypropyl methylcellulose, and the preparation method of excessive impregnation method was used to form an integrated adsorption with excellent adsorption performance. The agent is connected in series with the SCR treatment unit to achieve ultra-low emissions in the cold start stage of NOx.
It realizes ultra-low NOx emissions in the cold start stage of diesel vehicles, reduces the cost of adsorbent, improves the stability and recycling rate of adsorbents, simplifies the preparation process, and is suitable for industrial applications.
Smart Images

Figure CN119175069A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorbents, and specifically relates to an integral adsorbent based on 3D printing technology, a preparation method and a low-temperature cold start application thereof. Background Art
[0002] NOx during cold start of diesel vehicles x Emissions have always been an important challenge for environmental protection. During the cold start phase, the temperature of the engine and exhaust purification system is low, the incomplete combustion process and the low efficiency of the catalytic reaction lead to NO x Therefore, reducing NO emissions during the cold start phase of diesel vehicles x Emissions have significant environmental implications and engineering challenges.
[0003] Study on NO emission during cold start of diesel vehicles x Emissions involve multiple considerations. First, it is necessary to understand the working principle of diesel engine and exhaust purification system under cold start conditions, as well as the factors that affect their performance. Second, it is necessary to explore technical means to improve the engine combustion process and exhaust purification system to increase NO x In addition, factors such as fuel ratio, catalyst activity, and temperature control system need to be considered to influence NO conversion efficiency. x The impact of emissions and find effective control strategies.
[0004] In recent years, with the improvement of environmental protection requirements and the development of technology, the reduction of NOx during the cold start of diesel vehicles has become a hot topic. x Emission research has received increasing attention. Some progress has been made by improving engine control strategies, optimizing exhaust purification system design, and introducing new catalyst materials. However, further research and technological innovation are still needed to achieve more effective reduction of NO emissions during the cold start phase of diesel vehicles. x emissions, thereby protecting the environment and improving air quality.
[0005] To reduce NO during cold start x Emissions, passive NO x PNA adsorption technology came into being. PNA can absorb NO xAfter adsorption, the temperature rises and the nitrogen oxides are released to the downstream selective catalytic reduction unit (SCR) for catalytic conversion. Molecular sieves loaded with precious metal palladium are the most widely studied PNA materials, which have excellent adsorption capacity and resistance to chemical poisoning. However, the high cost of precious metal catalysts is an important factor restricting their widespread application. First, the rarity and preciousness of precious metals themselves lead to their high prices. The market prices of precious metals such as palladium, gold, platinum, and rhodium are high, which directly affects the preparation cost of precious metal adsorbents. Secondly, the preparation of high-performance precious metal adsorbents requires complex processes and precise control, which also increases their cost. From the selection of raw materials, the synthesis of adsorbents to subsequent processing and characterization, each step requires a lot of resources and time. In addition, the recovery and reuse of precious metal catalysts also face technical difficulties and cost pressures. Since precious metal adsorbents are usually used under high temperature and high pressure conditions, their surface activity is easily contaminated or inactivated, and they need to be replaced or regenerated regularly, and these processes require additional cost expenditures. Therefore, researchers have been working hard to find ways to reduce the cost of adsorbents, including developing new synthesis strategies, designing efficient carrier materials, and improving the stability and recycling rate of adsorbents, in order to achieve wider application of PNA adsorbents in industrial production.
[0006] Based on this, some researchers have turned their attention to non-precious metal-loaded materials, such as non-precious metal-loaded molecular sieve adsorbents and oxides of Mn, Co, Ni, and Ce. Among them, Mn / Al2O3 powder material is a non-precious metal-loaded material with excellent performance.
[0007] 3D printing technology is an advanced manufacturing technology that converts digital models into physical objects, also known as additive manufacturing. Compared with traditional subtractive manufacturing, 3D printing technology has many advantages. For example, (1) 3D printing technology can customize and manufacture products according to needs to meet personalized needs. This is very useful in the fields of medicine, consumer goods, automobiles, etc. (2) Traditional manufacturing methods may take weeks or even months to make prototypes, while 3D printing technology can make prototypes in a few hours or less, thereby accelerating the product development cycle. (3) Traditional processing methods usually require cutting raw materials into the desired shape, while 3D printing technology manufactures products by stacking materials layer by layer, so a lot of materials can be saved. (4) Traditional manufacturing methods usually require multiple processing steps, such as milling, turning, casting, etc., while 3D printing technology can integrate these steps into one process, thereby reducing production links and production time. (5) 3D printing technology can manufacture products with complex geometric structures, which is difficult to achieve with traditional processing methods. This capability is very important in the fields of aerospace, medical and engineering. (6) 3D printing technology can reduce waste and energy consumption because it typically uses precise amounts of material and can utilize recycled materials.
[0008] However, due to the poor fluidity of Mn / Al2O3 powder materials, there will be problems such as uneven catalyst block structure, poor shaping or poor mechanical strength when prepared by 3D printing. Therefore, combined with 3D printing technology, a monolithic non-precious metal adsorbent was developed and connected in series with the downstream SCR treatment unit to achieve NO x Ultra-low emissions during the cold start phase has become a problem that needs to be solved. Summary of the invention
[0009] In view of this, the technical problem to be solved by the present invention is to provide a monolithic adsorbent based on 3D printing technology, a preparation method and a low-temperature cold start application thereof. The present invention can realize 3D printing of Mn / Al2O3 powder to prepare a monolithic non-precious metal adsorbent, and connect it in series with the downstream SCR treatment unit to achieve NO x Ultra-low emissions during the cold start phase.
[0010] The present invention provides a monolithic adsorbent based on 3D printing technology, which is prepared by 3D printing from the following raw materials in parts by weight:
[0011] 8 to 18 parts by mass of Mn / Al2O3 powder;
[0012] 1 to 6 parts by weight of halloysite nanotubes;
[0013] 0.1 to 1 parts by mass of hydroxypropyl methylcellulose;
[0014] 80 to 90 parts by mass of solvent.
[0015] Preferably, in the Mn / Al2O3 powder, the manganese loading is 0.1-20wt.%, preferably 5wt.%;
[0016] The preparation method of the Mn / Al2O3 powder comprises one of an excess impregnation method, an equal volume impregnation method, and a solid grinding method;
[0017] Preferably, the method for preparing the Mn / Al2O3 powder comprises the following steps:
[0018] Al2O3 and manganese salt are mixed in a solvent for reaction, and after removing the solvent, the mixture is dried and calcined to obtain Mn / Al2O3 powder;
[0019] Preferably, the manganese salt is selected from manganese nitrate, manganese acetate, manganese sulfate and manganese chloride.
[0020] Preferably, before mixing Al2O3 and manganese salt in a solvent, the Al2O3 is also subjected to rare earth modification, and the rare earth metal element is one or more of La, Pr, Nd, Y, Ce, Zr, Sm, Pm, Eu, and Gd, and the loading amount of the rare earth metal element is 0.2wt.%-5.0wt.%.
[0021] Preferably, the solvent is selected from ethanol.
[0022] The present invention also provides a method for preparing the above-mentioned monolithic adsorbent, comprising the following steps:
[0023] A) mixing Mn / Al2O3 powder, halloysite nanotubes and a solvent, and heating to obtain a paste-like mixture;
[0024] The paste mixture is mixed with hydroxypropyl methylcellulose to obtain a 3D printing material;
[0025] B) placing the 3D printing material in a 3D printer, establishing a path by computer programming, and stacking the extruded Mn / Al2O3 fibers into a desired shape through a 3D printing system to obtain a monolithic adsorbent precursor;
[0026] C) drying and calcining the monolithic adsorbent precursor to obtain a monolithic adsorbent;
[0027] Alternatively, include the following steps:
[0028] a) mixing Al2O3, manganese salt and halloysite nanotubes in a solvent and heating to obtain a paste-like mixture;
[0029] The paste mixture is mixed with hydroxypropyl methylcellulose to obtain a 3D printing material;
[0030] b) placing the 3D printing material in a 3D printer, establishing a path by computer programming, and stacking the extruded Mn / Al2O3 fibers into a desired shape through a 3D printing system to obtain a monolithic adsorbent precursor;
[0031] c) drying the monolithic adsorbent precursor and then calcining it to obtain a monolithic adsorbent.
[0032] Preferably, the heating temperature is 60-100° C.; the calcining temperature is 500-650° C., and the calcining time is 4-8 hours.
[0033] The present invention also provides a method for realizing NO x Application in ultra-low emissions during cold start phase.
[0034] The present invention also provides a coaxial 3D printed tandem catalyst, comprising a coaxially arranged core and a shell, wherein the core is selected from the material of the above-mentioned monolithic adsorbent, and the shell is an oxide selective catalytic reduction unit.
[0035] Preferably, the main material of the shell layer is selected from one or more of Cu-SSZ-13, Cu-SSZ-39, Cu-SAPO-18, Cu-SAPO-34, Fe-SSZ-13, Fe-SSZ-39, V2O5-WO3(MoO3) / TiO2;
[0036] Preferably, the mass ratio of the core to the shell is 4:1 to 1:4;
[0037] Preferably, the method for preparing the coaxial 3D printed tandem catalyst comprises the following steps:
[0038] 1) configuring the core and the shell into 3D printing materials respectively;
[0039] Mixing Mn / Al2O3 powder, halloysite nanotubes and a solvent, and heating to obtain a paste mixture; mixing the paste mixture with hydroxypropyl methylcellulose (HPMC) and stirring to obtain a core 3D printing material;
[0040] The shell layer main material, halloysite nanotubes and a solvent are mixed and heated to obtain a paste mixture; the paste mixture is mixed and stirred with hydroxypropyl methylcellulose (HPMC) to obtain a shell layer 3D printing material;
[0041] 2) Extruding the core 3D printing material and the shell 3D printing material through a coaxial needle of a 3D printing system and stacking them into a desired shape to obtain a coaxial catalyst precursor;
[0042] 3) drying the coaxial catalyst precursor and then calcining it to obtain a coaxial catalyst.
[0043] The present invention also provides a method for realizing NO x Application in ultra-low emissions during cold start phase.
[0044] Compared with the prior art, the present invention provides a monolithic adsorbent based on 3D printing technology, which is prepared by 3D printing from the following raw materials by mass: 8% to 18% by mass of Mn / Al2O3 powder; 1% to 6% by mass of halloysite nanotubes; 0.1% to 1% by mass of hydroxypropyl methylcellulose (HPMC); 80% to 90% by mass of solvent. The present invention selects halloysite nanotubes and hydroxypropyl methylcellulose (HPMC) as binders. Halloysite nanotubes have excellent high temperature resistance, hardness and durability, and chemical stability, which can meet the application requirements of catalysts under high temperature and complex working conditions, and keep the catalyst structure mechanically stable. Hydroxypropyl methylcellulose (HPMC) has processability and plasticity, which can help print out complex shapes and structures, and is suitable for printing applications requiring high precision and complex design. Its super strong bonding force and interlayer bonding can effectively bond the printed materials, ensure the firmness and stability of interlayer attachment during printing, and help reduce distortion and deformation during printing. The Mn / Al2O3 monolithic passive NO was constructed in one step by 3D printing technology. x The preparation method of the adsorbent is simple and feasible. In view of the high cost and limited adsorption capacity of existing passive nitrogen oxide adsorbents, an economically efficient non-precious metal adsorbent is developed and connected in series with the downstream SCR treatment unit to achieve NO x Ultra-low emissions during the cold start phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is the X-ray diffraction spectrum of Mn(x) / Al2O3 with different Mn loading amounts (Example 1), (x) represents the Mn loading amount;
[0046] Figure 2 is the X-ray photoelectron spectrum of Mn(x) / Al2O3 (Example 1);
[0047] Figure 3 is the hydrogen-programmed temperature reduction diagram of Mn(x) / Al2O3 (Example 1);
[0048] Figure 4 is the UV-visible diffuse reflectance spectrum of Mn(x) / Al2O3 (Example 1);
[0049] Figure 5 A picture of a 3D printed Mn(x) / Al2O3 block (Example 2);
[0050] Figure 6 NO for Mn(x) / Al2O3 x Concentration curve change diagram (application example 1);
[0051] Figure 7 NO for Mn(x) / Al2O3x Adsorption capacity bar graph (Application Example 1);
[0052] Figure 8 NO is a rare earth metal doped Mn(2) / M-Al2O3 x Concentration curve change diagram (Example 3), M represents rare earth metal;
[0053] Fig. 9 NO for rare earth metal doped Mn(2) / Al2O3 x Adsorption capacity bar graph (Example 3);
[0054] Fig.10 a is a picture showing a change in the printing ink ratio based on Example 2 (Comparative Example 2);
[0055] Fig.10 b is a picture without adding inorganic binder (Comparative Example 3);
[0056] Fig.10 c is a picture without adding organic binder (Comparative Example 4);
[0057] Fig.11 This is a cross-sectional electron microscope image of the ink prepared based on Example 2 with ethanol replaced by water (Comparative Example 5);
[0058] Fig.12 A picture of a monolithic adsorbent made by 3D printing after physically mixing Al2O3 with manganese oxides (MnO2, Mn2O3, Mn3O4, MnO) (Comparative Example 6);
[0059] Fig.13 The NO2-absorbing agent of the monolithic adsorbent is made by 3D printing after physical mixing of Al2O3 and manganese oxides (MnO2, Mn2O3, Mn3O4, MnO). x Concentration curve change diagram (comparative application example 1);
[0060] Fig.14 NO of 2.0wt.% Pd-loaded Al2O3 (Pd(2) / Al2O3) and 2.0wt.% Pd-loaded SSZ-13 (Pd(2) / SSZ-13) with Mn(2) / Al2O3 x Concentration curve change diagram (comparative application example 2);
[0061] Fig.15 The images of catalysts formed by coaxial 3D printing core-shell structure, cordierite double-layer coating and physical mixing of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 (Application Example 2, Application Example 3 and Application Example 4);
[0062] Fig.16Cross-sectional electron scanning electron microscope images of catalysts formed by coaxial 3D printing core-shell structure, cordierite double-layer coating and physical mixing of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 (Application Example 2, Application Example 3 and Application Example 4);
[0063] Fig.17 The NO2 emission of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 in dry conditions was investigated by combining coaxial 3D printed core-shell structure, cordierite double-layer coating and physical mixing. x Concentration curve change diagram (Application Example 2, Application Example 3 and Application Example 4);
[0064] Fig.18 The NO2 emission of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 in the presence of 5% H2O was investigated by combining the coaxial 3D printed core-shell structure, cordierite double-layer coating and physical mixing. x Concentration curve change diagram (Application Example 2, Application Example 3 and Application Example 4).
[0065] Fig.19 NO for Mn / Al2O3 in three forms: 3D printing, cordierite coating and powder x Concentration curve change diagram;
[0066] Fig. 20 The NO of Mn / Al2O3 blocks prepared by replacing the inorganic binder halloysite nanotubes with bentonite x Histogram of adsorption / desorption capacity. DETAILED DESCRIPTION
[0067] The present invention provides a monolithic adsorbent based on 3D printing technology, which is prepared by 3D printing from the following raw materials in parts by weight:
[0068] 8 to 18 parts by mass of Mn / Al2O3 powder;
[0069] 1 to 6 parts by weight of halloysite nanotubes;
[0070] 0.1 to 1 parts by mass of hydroxypropyl methylcellulose (HPMC);
[0071] 80 to 90 parts by mass of solvent.
[0072] The raw materials for preparing the integral adsorbent based on 3D printing technology provided by the present invention include 8 to 18 parts by mass of Mn / Al2O3 powder, which can be 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, or any value between 8 and 18 parts by mass.
[0073] The preparation method of the Mn / Al2O3 powder comprises one of an excess impregnation method, an equal volume impregnation method and a solid grinding method.
[0074] In some specific embodiments of the present invention, the method for preparing the Mn / Al2O3 powder comprises the following steps:
[0075] Al2O3 and manganese salt are mixed in a solvent for reaction, and after removing the solvent, the mixture is dried and calcined to obtain Mn / Al2O3 powder.
[0076] Wherein, the manganese salt is selected from one of manganese nitrate, manganese acetate, manganese sulfate and manganese chloride, and is preferably manganese acetate.
[0077] Wherein, the reaction temperature is room temperature, and in the present invention, room temperature is defined as 25±5°C. The method of removing the solvent is heating to evaporate the water. The drying is drying, and after drying, the calcination temperature is 500-650°C, which can be 500, 550, 600, 650, or any value between 500-650°C, and the calcination time is 4-8h, which can be 4, 5, 6, 7, 8, or any value between 4-8h.
[0078] Before mixing Al2O3 with manganese salt in a solvent, the method also includes rare earth modification of the Al2O3, wherein the rare earth metal element is one or more of La, Pr, Nd, Y, Ce, Zr, Sm, Pm, Eu, and Gd, and the loading amount of the rare earth metal element is 0.2wt.% to 5.0wt.%, and can be 0.2wt.%, 0.5wt.%, 0.8wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, or any value between 0.2wt.% and 5.0wt.%.
[0079] On the one hand, the modified material can adjust the desorption behavior of Mn / Al2O3 so that the desorption temperature is within the optimal desorption temperature range; on the other hand, it can further improve the adsorption performance of Mn / Al2O3 by providing new adsorption sites or improving the dispersion of active sites. The specific modification method is the equal volume impregnation method.
[0080] In the present invention, the manganese loading in the Mn / Al2O3 powder is 0.1-20wt.%, and can be 0.1, 0.5, 0.6, 0.7, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or any value between 0.1 and 20wt.%, preferably 5wt.%.
[0081] The raw materials for preparing the monolithic adsorbent based on 3D printing technology provided by the present invention also include 1 to 6 parts by mass of halloysite nanotubes, which can be 1, 2, 3, 4, 5, 6, or any value between 1 and 6 parts by mass.
[0082] The raw materials for preparing the monolithic adsorbent based on 3D printing technology provided by the present invention also include 0.1 to 1 parts by mass of hydroxypropyl methylcellulose (HPMC), which can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any value between 0.1 and 1 parts by mass.
[0083] The raw materials for preparing the monolithic adsorbent based on 3D printing technology provided by the present invention also include 80 to 90 parts by mass of a solvent, which can be 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, or any value between 80 and 90 parts by mass. Preferably, the solvent is selected from ethanol. Ethanol can not only be used as a solvent, but also has high safety and low boiling point. Ethanol can also act as a defoaming agent to avoid interference from bubbles during printing and ensure the structural stability and consistency of the monolithic catalyst.
[0084] Monolithic catalysts generally refer to those monolithic catalysts with many narrow, straight or curved parallel channels. Since the cross section of the ceramic carrier catalyst developed in the early stage is a honeycomb structure, it is also called a honeycomb catalyst. In the present invention, the monolithic catalyst is a monolithic catalyst with a honeycomb structure in cross section.
[0085] The present invention also provides a method for preparing the above-mentioned monolithic adsorbent, comprising the following steps:
[0086] A) mixing Mn / Al2O3 powder, halloysite nanotubes and a solvent, and heating to obtain a paste-like mixture;
[0087] The paste mixture is mixed with hydroxypropyl methylcellulose (HPMC) to obtain a 3D printing material;
[0088] B) placing the 3D printing material in a 3D printer, establishing a path by computer programming, and stacking the extruded Mn / Al2O3 fibers into a desired shape through a 3D printing system to obtain a monolithic adsorbent precursor;
[0089] C) drying the monolithic adsorbent precursor and then calcining it to obtain a monolithic adsorbent.
[0090] The present invention first mixes Mn / Al2O3 powder, halloysite nanotubes and a solvent, wherein the mixing is preferably ultrasonic mixing, and then heating is performed, wherein the heating is preferably water bath heating at 60 to 100° C., and the heating temperature can be 60, 70, 80, 90, 100, or any value between 60 and 100° C. Finally, a paste mixture is obtained.
[0091] Then, the paste mixture is mixed with hydroxypropyl methylcellulose (HPMC) and stirred until the Mn / Al2O3 ink can be smoothly printed through the needle to obtain a 3D printing material.
[0092] Next, the 3D printing material is placed in a 3D printer, a path is established by computer programming, and the extruded Mn / Al2O3 fibers are stacked into a desired shape through a 3D printing system to obtain a monolithic adsorbent precursor.
[0093] Specifically, the Mn / Al2O3 ink is squeezed out from the stainless steel bayonet needle by a pneumatic jet 3D printing system, and stacked to form a desired shape to obtain a monolithic adsorbent precursor. The model of the needle is adjusted according to needs.
[0094] The monolithic adsorbent precursor is dried and then calcined to obtain a monolithic adsorbent. The calcination temperature is 500-650° C., which can be 500, 550, 600, 650, or any value between 500-650° C., and the calcination time is 4-8 hours, which can be 4, 5, 6, 7, 8, or any value between 4-8 hours.
[0095] The present invention also provides a method for realizing NO x Application in ultra-low emissions during cold start phase.
[0096] The present invention also provides a coaxial 3D printed tandem catalyst, with Mn / Al2O3 as a core and a shell layer coated on the surface of the core.
[0097] The core is prepared from Mn / Al2O3 powder, halloysite nanotubes, hydroxypropyl methylcellulose and solvent.
[0098] The shell is an oxide selective catalytic reduction unit (SCR). The main material of the shell is selected from one or more of Cu-SSZ-13, Cu-SSZ-39, Cu-SAPO-18, Cu-SAPO-34, Fe-SSZ-13, Fe-SSZ-39, V2O5-WO3(MoO3) / TiO2. The mass ratio of the core to the shell is 4:1 to 1:4, which can be 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, or any value between 4:1 and 1:4.
[0099] Compared with the existing tandem methods (such as cordierite double-layer coating or physical mixing), the tandem catalyst obtained by the coaxial 3D printing method has enhanced catalytic activity and nitrogen selectivity. x It is adsorbed and stored, and then desorbed and released to the shell SCR unit at high temperature, thereby improving the catalytic activity. In addition, the shell tightly wraps the core layer, which can effectively protect the core layer from the influence of deactivation factors in the environment and extend the service life of the adsorbent. On the other hand, the shell can limit the diffusion path of reactants and products, effectively inhibit the occurrence of side reactions, and improve the efficiency and selectivity of the denitrification process.
[0100] The series catalyst is a coaxial catalyst, and the specific preparation method comprises the following steps:
[0101] The core and the shell are configured into 3D printing materials respectively, wherein the configuration method of the core 3D printing material is as described above and will not be repeated here. The configuration method of the shell 3D printing material can preferably be configured according to the configuration method of the core layer. Specifically, the shell main material, halloysite nanotubes and solvent are mixed and heated to obtain a paste mixture; the paste mixture is mixed and stirred with hydroxypropyl methylcellulose (HPMC) to obtain the shell 3D printing material.
[0102] Then, the core 3D printing material and the shell 3D printing material are extruded through the coaxial needle of the 3D printing system and stacked into a desired shape to obtain a coaxial catalyst precursor.
[0103] The coaxial catalyst precursor is dried and then calcined to obtain a coaxial catalyst.
[0104] The calcination temperature is 500-650°C, and can be 500, 550, 600, 650, or any value between 500-650°C. The calcination time is 4-8h, and can be 4, 5, 6, 7, 8, or any value between 4-8h.
[0105] The present invention also provides a method for realizing NO x Application in ultra-low emissions during cold start phase.
[0106] Cold start means starting the engine after it has been turned off for a while and the engine has cooled down to a temperature lower than the normal operating temperature and a lot of oil has basically returned. Generally speaking, it can be measured by the ambient temperature. When the engine temperature slowly cools down to below 40℃ after it is turned off, it usually takes about 2 hours. Then starting it again at this time is called a cold start.
[0107] The present invention provides a non-precious metal adsorbent based on 3D printing technology, including a preparation method thereof and application in low-temperature cold start of automobiles. The preparation method of the adsorbent is flexible and easy to implement, has excellent adsorption / desorption performance, and has high economic benefits and industrial application potential.
[0108] In order to further understand the present invention, the integral adsorbent based on 3D printing technology, the preparation method and the low-temperature cold start application thereof provided by the present invention are described below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0109] Example 1
[0110] Mn / Al2O3 was prepared by excess impregnation method, and the metal precursor was manganese acetate. The theoretical loading of Mn was 1.0wt.%, 2.0wt.%, 3.0wt.%, 5.0wt.%, and 10.0wt.%. The carrier for synthesizing Mn / Al2O3 was commercial Al2O3 (Aladdin Reagent (Shanghai) Co., Ltd.).
[0111] The general preparation method is: 10g Al2O3 is mixed with 40mL manganese solution, ultrasonicated for 30 minutes, stirred at room temperature for 8 hours, and evaporated on a heated stirring table. Then, it is dried in an oven at 80℃ and calcined in a muffle furnace at 600℃ for 5 hours to obtain Mn(x) / Al2O3 powder.
[0112] See also Figures 1 to 4 , Figure 1 is an X-ray diffraction spectrum of Mn(x) / Al2O3 with different Mn loadings (Example 1), (x) represents the Mn loading, i.e., x=1 represents a loading of 1.0 wt.%, x=2 represents a loading of 2.0 wt.%, x=3 represents a loading of 3.0 wt.%, x=5 represents a loading of 5.0 wt.%, and x=10 represents a loading of 10.0 wt.%;
[0113] Figure 2 is the X-ray photoelectron spectrum of Mn(x) / Al2O3 (Example 1), indicating that Mn in Mn(x) / Al2O3 has three oxidation states, namely +2, +3, and +4;
[0114] Figure 3 is a hydrogen-programmed temperature reduction diagram of Mn(x) / Al2O3 (Example 1), in which the reduction peaks appearing in the diagram correspond to the reduction of MnO2—Mn2O3—Mn3O4—MnO;
[0115] Figure 4 is the UV-visible diffuse reflectance spectrum of Mn(x) / Al2O3 (Example 1), indicating that the existence form of Mn in Mn(x) / Al2O3 is Mn ion and Mn oxide;
[0116] Example 2
[0117] 8.0 g of the Mn / Al2O3 powder in Example 1, 2.0 g of halloysite nanotubes and 40 mL of ethanol were weighed and added to a glass beaker. After ultrasonic dispersion for 30 min, the mixture was placed in a 70°C water bath to form a viscous paste. Subsequently, 3.0 g of hydroxypropyl methylcellulose (HPMC) (3.0 wt.%) was added to the thick paste and stirred with a glass rod until the Mn / Al2O3 ink could be smoothly printed through the needle.
[0118] The Mn / Al2O3 ink was extruded from a stainless steel bayonet needle (19G) by a pneumatic jet 3D printing system and stacked to form honeycomb cylinders with a diameter of about 9 mm and a height of about 0.5 cm. After natural drying, the 3D printed Mn / Al2O3 block was calcined at 600 °C in air for 5 h to remove hydroxypropyl methylcellulose (HPMC) and maintain structural stability.
[0119] Figure 5 This is a picture of a 3D printed Mn(x) / Al2O3 block (Example 2). It can be seen from the figure that the cylindrical block is a honeycomb with cross channels and a diameter of about 9 mm.
[0120] Example 3
[0121] Example 3 is based on Example 1. Before excessive impregnation with Mn, Al2O3 is first modified with rare earth metals. The selected rare earth metals are La, Pr, Nd, and Y. The modification method is excessive impregnation. The modified Mn / Al2O3 is marked as M-Al2O3. The preparation of Mn(2) / M-Al2O3 refers to the preparation method of 2.0wt.% Mn / Al2O3 in Example 1. Then, referring to Example 2, Mn(2) / M-Al2O3 is 3D printed to form an integral adsorbent similar to Mn / Al2O3, that is, only "Mn / Al2O3" in Example 2 is replaced by "Mn(2) / M-Al2O3" and other conditions remain unchanged.
[0122] Example 4
[0123] Example 4 is based on Example 1, and the manganese metal precursor is replaced by one of manganese nitrate, manganese chloride and manganese sulfate, and the loading amount of Mn is 1.0wt.%, 2.0wt.%, 3.0wt.%, 5.0wt.% and 10.0wt.%, respectively.
[0124] Example 5
[0125] Example 5 The catalyst preparation method is further simplified based on Example 1 and Example 2, and Mn / Al2O3 is printed in one step. The specific operation is as follows: 8g Al2O3 is mixed with 40mL manganese salt solution, ultrasonicated for 30 minutes, stirred at room temperature for 8 hours, and then 2.0g halloysite nanotubes are added and evaporated on a heated stirring table to form a viscous paste. Subsequently, 3.0g of hydroxypropyl methylcellulose (HPMC) (3.0wt.%) is added to the thick slurry, 2mL of ethanol is added as a defoamer, and stirring with a glass rod is continued until the ink can be smoothly printed through the needle. The Mn / Al2O3 ink is squeezed out of a stainless steel bayonet needle (19G) by a pneumatic jet 3D printing system, and stacked to form a honeycomb cylinder with a diameter of about 9 mm and a height of about 0.5 cm. After natural drying, the 3D-printed Mn / Al2O3 block is calcined at 600°C in air for 5 hours to remove hydroxypropyl methylcellulose (HPMC) and maintain structural stability.
[0126] Example 6
[0127] Example 6 Based on Example 5, the preparation of the catalyst is further optimized, and one or more rare earth metal salts (cerium nitrate, zirconium nitrate, lanthanum nitrate, samarium nitrate, praseodymium nitrate, neodymium nitrate, yttrium nitrate, etc.) are added to the manganese solution to increase the mechanical strength of the block. The loading amount of the rare earth metal is 1.0wt.%.
[0128] Comparative Example 1
[0129] Weigh 2.0g Al2O3 and 158.2mg MnO2 (or 143.7mg Mn2O3, or 138.8mg Mn3O4, or 129.1mg MnO), 0.5g Halloysite nanotubes and 10mL of ethanol into a glass beaker. After ultrasonic dispersion for 30min, place in a 70°C water bath to form a viscous paste. Subsequently, 1.0g of hydroxypropyl methylcellulose (HPMC) (3.0wt.%) is added to the thick slurry and stirred with a glass rod until the ink flows smoothly through the needle to print. The ink is squeezed out of the needle (19G) by a pneumatic jet 3D printing system and stacked to form a honeycomb cylinder with a diameter of about 9 mm and a height of about 0.5 cm. After natural drying, calcined at 600°C in air for 5 hours to remove the organic binder and maintain structural stability. The prepared adsorbents were labeled: MnO2+Al2O3, Mn2O3+Al2O3, Mn3O4+Al2O3, and MnO+Al2O3. Fig.12 This is a picture of a monolithic adsorbent made by 3D printing after physically mixing Al2O3 and manganese oxides (MnO2, Mn2O3, Mn3O4, MnO) (Comparative Example 1). It can be seen from the figure that the cylindrical block is in the shape of a honeycomb with cross channels and has a diameter of about 9 mm.
[0130] Comparative Example 2
[0131] Comparative Example 2 Based on Example 2, the ratio of the ink used for printing was adjusted. 8.0 g of the Mn / Al2O3 powder, 0.5 g of halloysite nanotubes and 40 mL of ethanol in Example 1 were weighed and added to a glass beaker. After ultrasonic dispersion for 30 min, it was placed in a 70°C water bath to form a viscous paste. Subsequently, 1 g of hydroxypropyl methylcellulose (HPMC) (3.0 wt.%) was added to the thick paste and stirred with a glass rod until the Mn / Al2O3 ink could be smoothly printed through the needle.
[0132] See also Fig.10 a, Fig.10 a is a picture showing a change in the printing ink ratio based on Example 2 (Comparative Example 2). Fig.10 b is a picture without adding inorganic binder (Comparative Example 3); Fig.10 c is a picture without adding organic binder (Comparative Example 4); it can be seen from the figure that changing the printing ink ratio or not adding binder will reduce the mechanical properties of the block.
[0133] Comparative Example 3
[0134] Comparative Example 3 is based on Example 2, but no halloysite nanotubes are added when preparing the printing ink. 8.0 g of the above-mentioned Mn / Al2O3 powder and 40 mL of ethanol in Example 1 are weighed and added to a glass beaker. After ultrasonic dispersion for 30 minutes, it is placed in a 70°C water bath to form a viscous paste. Subsequently, 3 g of hydroxypropyl methylcellulose (HPMC) (3.0 wt.%) is added to the thick slurry and stirred with a glass rod until the Mn / Al2O3 ink can be smoothly printed through the needle.
[0135] Comparative Example 4
[0136] Comparative Example 4 Based on Example 2, hydroxypropyl methylcellulose (HPMC) was not added when preparing the printing ink. 8.0 g of the Mn / Al2O3 powder in Example 1, 2.0 g of halloysite nanotubes and 40 mL of ethanol were weighed and added to a glass beaker. After ultrasonic dispersion for 30 minutes, the mixture was placed in a 70°C water bath to form a viscous paste.
[0137] Comparative Example 5
[0138] Comparative Example 5 is based on Example 2, and the solvent ethanol is replaced with water when preparing the printing ink. 8.0g of the above-mentioned Mn / Al2O3 powder, 2.0g of halloysite nanotubes and 40mL of water in Example 1 are weighed and added to a glass beaker. After ultrasonic dispersion for 30 minutes, it is placed in a 70°C water bath to form a viscous paste. Subsequently, 3.0g of hydroxypropyl methylcellulose (HPMC) (3.0wt.%) is added to the thick slurry and stirred with a glass rod until the Mn / Al2O3 ink can be smoothly printed through the needle. Fig.11 This is a cross-sectional electron microscope image of the ink prepared based on Example 2, in which ethanol is replaced with water (Comparative Example 5). As can be seen from the figure, bubbles (black frame) are formed after ethanol is replaced with water.
[0139] Comparative Example 6
[0140] Preparation and printing of Pd(2) / Al2O3: The preparation of Pd(2) / Al2O3 adopts a method similar to that of Mn(2) / Al2O3. The metal precursor solution is a palladium chloride solution. The theoretical loading of Pd is 2.0wt.%. The carrier for synthesizing Mn / Al2O3 is commercial Al2O3 (Aladdin Reagent (Shanghai) Co., Ltd.). The general preparation method is: 2g Al2O3 is mixed with 10mL palladium chloride solution, ultrasonicated for 30 minutes, stirred at room temperature for 8 hours, and the water is evaporated on a heated stirring table. Then it is dried in an oven at 80°C and calcined in a muffle furnace at 600°C for 5 hours to obtain Mn / Al2O3 powder. The printing of Pd(2) / Al2O3 adopts the same method as that of Mn(2) / Al2O3, which will not be repeated.
[0141] Preparation and printing of Pd(2) / SSZ-13: The preparation of Pd(2) / SSZ-13 was similar to that of Pd(2) / Al2O3. The difference was that the carrier Al2O3 was replaced by SSZ-13 (Nankai University Catalyst Plant). The printing method of Pd(2) / SSZ-13 was the same as that of Pd(2) / Al2O3.
[0142] Comparative Example 7
[0143] Comparative Example 7 is based on Example 2, and the inorganic binder halloysite nanotubes are replaced with bentonite. 8.0 g of the above-mentioned Mn / Al2O3 powder in Example 1, 2.0 g of bentonite and 40 mL of ethanol are weighed and added to a glass beaker. After ultrasonic dispersion for 30 minutes, it is placed in a 70°C water bath to form a viscous paste. Subsequently, 3.0 g of HPMC gel (3.0 wt.%) is added to the thick slurry and stirred with a glass rod until the Mn / Al2O3 ink can be smoothly printed through the needle.
[0144] The Mn / Al2O3 ink was extruded from a stainless steel bayonet needle (19G) by a pneumatic jet 3D printing system and stacked to form honeycomb cylinders with a diameter of about 9 mm and a height of about 0.5 cm. After natural drying, the 3D printed Mn / Al2O3 block was calcined at 600 °C in air for 5 hours to remove the organic binder.
[0145] Comparative Example 8
[0146] Comparative Example 8 is based on Example 2, and the organic binder hydroxypropyl methylcellulose (HPMC) is replaced with polyvinyl alcohol. 8.0 g of the above-mentioned Mn / Al2O3 powder in Example 1, 2.0 g of halloysite nanotubes and 40 mL of ethanol are weighed and added to a glass beaker. After ultrasonic dispersion for 30 minutes, it is placed in a 70°C water bath to form a viscous paste. Subsequently, 3.0 g of polyvinyl alcohol (3.0 wt.%) is added to the thick slurry and stirred with a glass rod until the Mn / Al2O3 ink can pass through the needle smoothly.
[0147] The Mn / Al2O3 ink was extruded from a stainless steel bayonet needle (19G) by a pneumatic jet 3D printing system and stacked to form honeycomb cylinders with a diameter of about 9 mm and a height of about 0.5 cm. After natural drying, the 3D printed Mn / Al2O3 block was calcined at 600 °C in air for 5 hours to remove the organic binder.
[0148] Comparative Example 9
[0149] Comparative Example 9 is based on Example 2, and the inorganic binder halloysite nanotubes and the organic binder hydroxypropyl methylcellulose (HPMC) are replaced by bentonite and polyvinyl alcohol, respectively. 8.0 g of the above-mentioned Mn / Al2O3 powder in Example 1, 2.0 g of bentonite and 40 mL of ethanol are weighed and added to a glass beaker. After ultrasonic dispersion for 30 minutes, it is placed in a 70°C water bath to form a viscous paste. Subsequently, 3.0 g of polyvinyl alcohol (3.0 wt.%) is added to the thick slurry and stirred with a glass rod until the Mn / Al2O3 ink can pass through the needle smoothly.
[0150] The Mn / Al2O3 ink was extruded from a stainless steel bayonet needle (19G) by a pneumatic jet 3D printing system and stacked to form honeycomb cylinders with a diameter of about 9 mm and a height of about 0.5 cm. After natural drying, the 3D printed Mn / Al2O3 block was calcined at 600 °C in air for 5 hours to remove the organic binder.
[0151] Fig. 20 The NO of the prepared Mn / Al2O3 bulk was prepared by replacing the inorganic binder and the organic binder separately or simultaneously. xAdsorption capacity bar graph. As can be seen from the figure, the Mn / Al2O3 block prepared with halloysite nanotubes as inorganic binder and hydroxypropyl methylcellulose (HPMC) as organic binder has the highest NO x Adsorption capacity.
[0152] Application Example 1
[0153] The Mn / Al2O3 block prepared in Example 2 was used as a monolithic NO x Adsorbent. The activity evaluation device consists of a gas distribution and catalytic reaction experimental device and a Fourier transform infrared spectrometer. The gas flow rate is controlled by a mass flow meter in the gas distribution and catalytic reaction experimental device. Table 1 shows the gas composition and gas component concentration. The total gas flow rate is set to 200mL / min. The pretreatment and adsorption and desorption test process of the catalyst is completed in the reactor of the gas distribution and catalytic reaction experimental device. The reactor is equipped with a K-type thermocouple to monitor the temperature change during the reaction. The gas concentration at the outlet is analyzed by a Fourier transform infrared spectrometer. The specific test process is as follows: weigh 300mg Mn / Al2O3 block, place it in a quartz tube with a diameter of 1 cm, start the temperature control program, and heat it from room temperature to 500℃ at a heating rate of 10℃ / min, and pretreat it at 500℃ for 30min. After the pretreatment is completed, the reactor is cooled to 100℃ and kept at a constant temperature, and the gas route leading to the reaction tube is switched to bypass. After switching to the bypass, the gas flow rate was set according to the gas conditions required for the activity test in Table 1. After the concentration of the feed gas was stable, the gas route was switched from the bypass to the reaction tube. After 10 minutes of adsorption, the temperature was increased from 100°C to 500°C at a heating rate of 10°C / min. The concentration of the outlet gas was recorded by the MKS MultiGas 2030FTIR gas analyzer.
[0154] Table 1 Gas composition and concentration settings for pretreatment and adsorption-desorption tests
[0155]
[0156] See also Figure 6 and Figure 7 , Figure 6 NO for Mn(x) / Al2O3 x Concentration curve change diagram (Application Example 1). It can be seen from the figure that Mn(x) / Al2O3 with different Mn contents has the ability to quickly adsorb NO x , two obvious desorption peaks appeared; Figure 7 NO for Mn(x) / Al2O3 x Adsorption capacity bar graph (Application Example 1). It can be seen from the figure that the adsorption capacity of Mn(x) / Al2O3 with different Mn contents increases with the increase of Mn content;
[0157] The Mn(2) / M-Al2O3 block prepared in Example 3 was used as a monolithic NO x Adsorbent. The specific method is the same as above, and the results are shown in Figure 8 and Fig. 9 , Figure 8 NO is a rare earth metal doped Mn(2) / M-Al2O3 x Concentration curve change diagram (Example 3), M represents rare earth metal. It can be seen from the figure that after rare earth metal doping, the desorption temperature moves to high temperature, indicating that rare earth metal can optimize the desorption behavior of Mn / Al2O3. Fig. 9 NO for rare earth metal doped Mn(2) / Al2O3 x The adsorption capacity bar graph (Example 3) shows that the adsorption capacity is improved after rare earth metal doping.
[0158] Application Example 2
[0159] The coaxial 3D printing technology is used to connect the Mn / Al2O3 and Cu-SSZ-13 (Cu-SSZ-13 is prepared by ion exchange method) in Example 1 in series in the form of a core-shell structure, with Mn / Al2O3 as the core layer and Cu-SSZ-13 as the shell layer. First, the printing inks of Mn / Al2O3 and Cu-SSZ-13 are prepared respectively according to the preparation method of the ink in Example 2. The Mn / Al2O3 and Cu-SSZ-13 inks prepared above are extruded from a coaxial needle (20G / 16G) by a pneumatic jet 3D printing system, and stacked to form a honeycomb cylinder with a diameter of about 9 mm and a height of about 5 mm. Among them, the gas pressure of extruding Mn / Al2O3 in the core layer is 0.2Mpa, and the gas pressure of extruding Cu-SSZ-13 in the shell layer is 0.2Mpa. Among them, the core-shell ratio is 1:1. After natural drying, the 3D printed Mn / Al2O3@Cu-SSZ-13 block was calcined at 600°C in air for 5 hours to remove hydroxypropyl methylcellulose (HPMC) to obtain a structurally stable core-shell tandem catalyst. The mass of the catalyst during the test was 300 mg.
[0160] Fig.15 The images of catalysts formed by coaxial 3D printing core-shell structure, cordierite double-layer coating and physical mixing of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 (Application Example 2, Application Example 3 and Application Example 4);
[0161] Fig.16 Cross-sectional electron scanning electron microscopy image of the catalyst formed by coaxial 3D printing core-shell structure, cordierite double-layer coating and physical mixing of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 (Application Example 2( Fig.16 a) Application Example 3( Fig.16b) and Application Example 4( Fig.16 c));
[0162] Fig.17 The NO2 emission of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 in dry conditions was investigated by combining coaxial 3D printed core-shell structure, cordierite double-layer coating and physical mixing. x Concentration curve change diagram (Application Example 2, Application Example 3 and Application Example 4);
[0163] Fig.18 The NO2 emission of Mn / Al2O3 and SCR catalyst Cu-SSZ-13 in the presence of 5% H2O was investigated by combining the coaxial 3D printed core-shell structure, cordierite double-layer coating and physical mixing. x Concentration curve change diagram (Application Example 2, Application Example 3 and Application Example 4).
[0164] Application Example 3
[0165] Take 400 cpsi cordierite and cut it into a cylindrical shape with a length of about 23 mm and a diameter of about 9 mm ( Fig.15 ). The Mn / Al2O3 and Cu-SSZ-13 in Example 1 are coated on cordierite, with Mn / Al2O3 as the bottom layer and Cu-SSZ13 as the top layer, and 120 mg of powder and 30 mg of halloysite nanotubes are used for each layer. Single-layer Cu-SSZ-13 coating uses 240 mg of powder and 60 mg of halloysite nanotubes. The activity evaluation device consists of a gas distribution and catalytic reaction experimental device and a Fourier transform infrared spectrometer. The gas flow rate is controlled by a mass flowmeter in the gas distribution and catalytic reaction experimental device. Table 2 shows the gas composition and gas component concentration, and the total gas flow rate is set to 200 mL / min. The pretreatment and adsorption and desorption test process of the catalyst are completed in the reactor of the gas distribution and catalytic reaction experimental device. The reactor is equipped with a K-type thermocouple to monitor the temperature change during the reaction. The gas concentration at the outlet is analyzed by a Fourier transform infrared spectrometer. The specific test process is as follows: Place the coated cordierite in a quartz tube with a diameter of 1 cm, set the gas flow rate according to Table 2, and switch to the bypass. After the gas concentration is stable, start the temperature control program, increase the temperature from room temperature to 50°C at a rate of 10°C / min, switch the gas from the bypass to the sample tube, and at the same time increase the temperature from 50°C to 500°C at a rate of 15°C / min. NH3 is introduced at a temperature of 170°C. 5% H2O is introduced when necessary.
[0166] Table 2 Gas composition and concentration settings for pretreatment and adsorption-desorption tests
[0167]
[0168] Application Example 4
[0169] Weigh 2.0 g each of Mn / Al2O3 and Cu-SSZ-13 powder, 1.0 g of halloysite nanotubes and 20 mL of ethanol into a glass beaker. After ultrasonic dispersion for 30 min, place in a 70°C water bath to form a viscous paste. Subsequently, add 2 g of hydroxypropyl methylcellulose (HPMC) to the thick paste and stir with a glass rod until the ink flows smoothly through the needle to print.
[0170] The ink was squeezed out of the needle (19G) by a pneumatic jet 3D printing system and stacked to form a honeycomb cylinder with a diameter of about 1 cm and a height of about 0.5 cm. After natural drying, it was calcined at 600°C in air for 5 hours to remove the binder and maintain structural stability.
[0171] The printing process of Cu-SSZ-13 block is the same as that of Mn / Al2O3. The activity test steps of the physical mixture of Mn / Al2O3 and Cu-SSZ-13 are the same as those in Application Example 2 and will not be repeated here. The mass of the catalyst during the test is 300 mg.
[0172] Application Example 5
[0173] Application Example 5 is based on Application Examples 2, 3, and 4, and replaces Cu-SSZ-13 with other denitrification catalysts, namely Cu-SSZ-39, Cu-SAPO-18, Cu-SAPO-34, Fe-SSZ-13, Fe-SSZ-39, V2O5-WO3(MoO3) / TiO2, etc., which are connected in series with Mn / Al2O3 in the three ways of Application Examples 2, 3, and 4.
[0174] Comparative application example 1
[0175] Similarly, MnO2+Al2O3, Mn2O3+Al2O3, Mn3O4+Al2O3, MO+Al2O3 in Comparative Example 1 were used as integral NO x The evaluation method is the same as the activity evaluation method of the Mn / Al2O3 block in Application Example 1.
[0176] Fig.13 The NO2-absorbing agent of the monolithic adsorbent is made by 3D printing after physical mixing of Al2O3 and manganese oxides (MnO2, Mn2O3, Mn3O4, MnO). x Concentration curve change diagram (Comparative Application Example 1). It can be seen from the figure that the physical mixture of Al2O3 and manganese oxide has poor adsorption activity at low temperature stage.
[0177] Comparative Application 2
[0178] Similarly, the Pd(2) / Al2O3 and Pd(2) / SSZ-13 blocks in Comparative Example 6 were used as monolithic NO x The evaluation method is the same as the activity evaluation method of the Mn / Al2O3 block in Application Example 1.
[0179] Fig.14 NO of 2.0wt.% Pd-loaded Al2O3 (Pd(2) / Al2O3) and 2.0wt.% Pd-loaded SSZ-13 (Pd(2) / SSZ-13) with Mn(2) / Al2O3 x The concentration curve change diagram (Comparative Application Example 2) shows that the adsorption activity of the non-precious metal adsorbent Mn(2) / Al2O3 is comparable to that of the precious metal Pd-loaded adsorbent.
[0180] Comparative Application 3
[0181] Comparative Example Application 3 is based on Application Example 1, and the activity of Mn / Al2O3 is evaluated in the form of cordierite coating and powder. The cordierite coating method refers to Application Example 3, and 400cpsi cordierite is cut into a cylinder with a length of about 23mm and a diameter of about 9mm. The Mn / Al2O3 in Example 1 is coated on the cordierite in multiple times, and the coating uses 240mg Mn / Al2O3 and 60mg halloysite nanotubes. The powder form adopts the traditional tablet press screening method, and the Mn / Al2O3 tablets are sieved into 60-80 mesh particles. The mass weighed during the test is 240mg.
[0182] Fig.19 NO for Mn / Al2O3 in three forms: 3D printing, cordierite coating and powder x Concentration curve change diagram. It can be seen from the figure that Mn / Al2O3 has the best NO adsorption activity by 3D printing.
[0183] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A monolithic adsorbent based on 3D printing technology, characterized in that: Prepared by 3D printing from the following raw materials in parts by weight: 8 to 18 parts by mass of Mn / Al2O3 powder; 1 to 6 parts by weight of halloysite nanotubes; 0.1 to 1 parts by mass of hydroxypropyl methylcellulose; 80 to 90 parts by mass of solvent.
2. The monolithic adsorbent according to claim 1, characterized in that: In the Mn / Al2O3 powder, the manganese loading is 0.1-20wt.%, preferably 5wt.%; The preparation method of the Mn / Al2O3 powder comprises one of an excess impregnation method, an equal volume impregnation method, and a solid grinding method; Preferably, the method for preparing the Mn / Al2O3 powder comprises the following steps: Al2O3 and manganese salt are mixed in a solvent for reaction, and after removing the solvent, the mixture is dried and calcined to obtain Mn / Al2O3 powder; Preferably, the manganese salt is selected from manganese nitrate, manganese acetate, manganese sulfate and manganese chloride.
3. The monolithic adsorbent according to claim 1, characterized in that: Before mixing Al2O3 and manganese salt in a solvent, the Al2O3 is also subjected to rare earth modification, wherein the rare earth metal element is one or more of La, Pr, Nd, Y, Ce, Zr, Sm, Pm, Eu, and Gd, and the loading amount of the rare earth metal element is 0.2wt.%-5.0wt.%.
4. The monolithic adsorbent according to claim 1, characterized in that: The solvent is selected from ethanol.
5. A method for preparing a monolithic adsorbent according to any one of claims 1 to 4, characterized in that: The following steps are involved: A) mixing Mn / Al2O3 powder, halloysite nanotubes and a solvent, and heating to obtain a paste-like mixture; The paste mixture is mixed with hydroxypropyl methylcellulose to obtain a 3D printing material; B) placing the 3D printing material in a 3D printer, establishing a path by computer programming, and stacking the extruded Mn / Al2O3 fibers into a desired shape through a 3D printing system to obtain a monolithic adsorbent precursor; C) drying and calcining the monolithic adsorbent precursor to obtain a monolithic adsorbent; Alternatively, include the following steps: a) mixing Al2O3, manganese salt and halloysite nanotubes in a solvent and heating to obtain a paste-like mixture; The paste mixture is mixed with hydroxypropyl methylcellulose to obtain a 3D printing material; b) placing the 3D printing material in a 3D printer, establishing a path by computer programming, and stacking the extruded Mn / Al2O3 fibers into a desired shape through a 3D printing system to obtain a monolithic adsorbent precursor; c) drying the monolithic adsorbent precursor and then calcining it to obtain a monolithic adsorbent.
6. The preparation method according to claim 5, characterized in that: The heating temperature is 60-100° C.; the calcining temperature is 500-650° C., and the calcining time is 4-8 hours.
7. A monolithic adsorbent as claimed in any one of claims 1 to 6 for achieving NO x Application in ultra-low emissions during cold start phase.
8. A coaxial 3D printed tandem catalyst, characterized in that: It comprises a core and a shell layer which are coaxially arranged, wherein the core is selected from the material of the monolithic adsorbent as claimed in any one of claims 1 to 6, and the shell layer is an oxide selective catalytic reduction unit.
9. The coaxial 3D printed tandem catalyst according to claim 8, characterized in that: The main material of the shell layer is selected from one or more of Cu-SSZ-13, Cu-SSZ-39, Cu-SAPO-18, Cu-SAPO-34, Fe-SSZ-13, Fe-SSZ-39, V2O5-WO3(MoO3) / TiO2; Preferably, the mass ratio of the core to the shell is 4:1 to 1:4; Preferably, the method for preparing the coaxial 3D printed tandem catalyst comprises the following steps: 1) configuring the core and the shell into 3D printing materials respectively; Mixing Mn / Al2O3 powder, halloysite nanotubes and a solvent, and heating to obtain a paste mixture; mixing the paste mixture with hydroxypropyl methylcellulose (HPMC) and stirring to obtain a core 3D printing material; The shell layer main material, halloysite nanotubes and solvent are mixed and heated to obtain a paste mixture; the paste mixture is mixed and stirred with hydroxypropyl methylcellulose (HPMC) to obtain a shell layer 3D printing material; 2) Extruding the core 3D printing material and the shell 3D printing material through a coaxial needle of a 3D printing system and stacking them into a desired shape to obtain a coaxial catalyst precursor; 3) drying the coaxial catalyst precursor and then calcining it to obtain a coaxial catalyst.
10. A coaxial 3D printed tandem catalyst as claimed in claim 8 or 9 for achieving NO x Application in ultra-low emissions during cold start phase.
Citation Information
Patent Citations
Method for preparing integrated molecular sieve blocks on basis of 3D printing technology
CN109160800A
Mn-modified Cu-SSZ-13 catalyst as well as preparation method and application thereof
CN112246277A
Cu-SAPO-34 / cordierite monolithic catalyst and preparation method thereof
CN116532152A
Composite material, preparation method thereof and nitrogen oxide adsorbent
CN118105938A
Method for producing catalyst monoliths
US20190381491A1
Cited By
Ultralow-temperature flue gas denitration forming catalyst based on 3D printing and preparation method thereof
CN120754841A
